2021
DOI: 10.1101/2021.11.29.469930
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Adolescent ethanol drinking promotes hyperalgesia, neuroinflammation and serotonergic deficits in mice that persist into adulthood

Abstract: Adolescent alcohol use can permanently alter brain function and lead to poor health outcomes in adulthood. Emerging evidence suggests that alcohol use predispose to pain disorders or exacerbate existing pain conditions, but the neural mechanisms are currently unknown. Here we report that mice exposed to adolescent intermittent access to ethanol (AIE) exhibit increased pain sensitivity and depressive-like behaviors that persist after alcohol cessation and are accompanied by elevated CD68 expression in microglia… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Comparatively little is known about the effects of alcohol on the median raphe (MR), although we recently found that chronic alcohol exposure during adolescence reduces 5-HT expression in both the DR and the MR [ 76 ]. This suggests that these two areas may be equally sensitive to the effects of alcohol, though surprisingly, chronic heavy alcohol use is not associated with loss of 5-HT neurons in the MR in humans [ 77 ].…”
Section: Alcohol’s Effects On Brainstem Monoaminergic Systems May Inc...mentioning
confidence: 99%
“…Comparatively little is known about the effects of alcohol on the median raphe (MR), although we recently found that chronic alcohol exposure during adolescence reduces 5-HT expression in both the DR and the MR [ 76 ]. This suggests that these two areas may be equally sensitive to the effects of alcohol, though surprisingly, chronic heavy alcohol use is not associated with loss of 5-HT neurons in the MR in humans [ 77 ].…”
Section: Alcohol’s Effects On Brainstem Monoaminergic Systems May Inc...mentioning
confidence: 99%